The Vitamin C Potential of Sorrel Tree (Averrhoa bilimbi) as LATEX Coagulant - Anam, Khairul; Kamelia, Marlina; Faridah, Indah (Biosfer: Jurnal Tadris Biologi, 2021)
This research aims to determine the vitamin C potential of tree sorrels (Averrhoa bilimbi) as a natural latex coagulant. The researchers employed the Completely Randomized Design (CRD) method. The method consisted of three repetitions with five treatments, namely negative control (without clotting) and positive control, by administering tree sorrel extract (Averrhoa bilimbi) with a volume of 5 ml, 10 ml, 15, and 20 ml. The researchers tested the vitamin C levels using UV-VIS Spectrophotometry DR 6000 with a wavelength of 265 nm to 271 nm. Furthermore, the data were analyzed using the One-Way ANOVA statistical test and the LSD to determine the most effective volume as a latex coagulant. The quantitative data were the clotting time and latex weight. The results showed that tree sorrel extract could be used as a latex coagulant. The fastest duration (1.18 minutes) and the highest weight (34.30 grams) of latex were found in the 20 ml volume. At the same time, the lowest yield was at a volume of 5 ml with a clotting time of 5.4 minutes and a weight of 18.62 grams.